2002
DOI: 10.2144/mar0205
|View full text |Cite
|
Sign up to set email alerts
|

ProteinChip ® Clinical Proteomics: Computational Challenges and Solutions

Abstract: ProteinChip technology, a suite of analytical tools that includes retentate chromatography, on-chip protein characterization, and multivariate analysis, allows researchers to examine patterns of protein expression and modification. Based on the surface enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) approach (17), ProteinChip technology has been pioneered by researchers at Ciphergen Biosystems (Fremont, CA, USA), as well as by users of Ciphergens commercial embodiment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 12 publications
(13 reference statements)
2
101
0
Order By: Relevance
“…Even more spectacular advances in mass spectrometry should be expected, with fur-ther improvements in resolution and detectability. With this in mind, it is not surprising that many scientists have decided to use mass spectrometry either as a diagnostic tool or as a cancer or other disease biomarker discovery platform (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Even more spectacular advances in mass spectrometry should be expected, with fur-ther improvements in resolution and detectability. With this in mind, it is not surprising that many scientists have decided to use mass spectrometry either as a diagnostic tool or as a cancer or other disease biomarker discovery platform (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The types of cancers that have been examined include ovarian, prostate, breast, bladder, renal, and others, and the biological fluids analyzed include serum, urine, cerebrospinal fluid, nipple aspirate fluid, etc. The apparent successes with this technology have been recently reviewed by many investigators (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In general, it has been suggested that this technology can achieve much higher diagnostic sensitivity and specificity (approaching 100%) in comparison to the classical cancer biomarkers (31).…”
Section: Mass Spectrometry As a Cancer Biomarker Discovery And Diagnomentioning
confidence: 99%
See 1 more Smart Citation
“…Many different techniques exist such as "Inverse Normalization" [36] or "Logarithmic Normalization" [25]. The most frequently used method is global normalization with respect to the average total ion current (TIC) [12,2]. The TIC is the sum of the area of all peaks in a spectra and as such quite insensitive to noise, because noise is mostly canceled out by the summation.…”
Section: Normalizationmentioning
confidence: 99%
“…The former is a modified version of matrix-assisted laser desorption/ionization-TOF MS (MALDI-TOF MS), in that it utilizes ProteinChip arrays for selective capture of chemically or biochemically distinct proteins from a mixed population (Fung & Enderwick, 2002). The protein arrays in SELDI-TOF MS are available with different types of receptors bound to their surface.…”
Section: Introductionmentioning
confidence: 99%